Factors influencing prolactin levels in chronic long-term hospitalized schizophrenic patients with co-morbid type 2 diabetes mellitus - Zhu, Junhong; Wang, Huijuan; Huang, Shaoyun; Zhang, Yingying; Liu, Xuebing; Li, Yi; Ma, Jun (Frontiers in Psychiatry, 2022)
Background For long-term hospitalized patients suffering from schizophrenia, metabolic disease and hyperprolactinemia (HPRL) are common comorbidities. This article is aimed at analyzing the factors influencing comorbid type 2 diabetes mellitus (T2DM) on prolactin (PRL) levels in long-term hospitalized patients suffering from schizophrenia. Methods This study included 378 long-term hospitalized patients with schizophrenia. Common metabolic markers and PRL levels of included samples were collected, and the severity of psychopathology was assessed using the Positive and Negative Symptoms Scale (PANSS). Based on the patients with or without T2DM, the samples were divided into two groups. The differences in clinical parameters between the two groups were compared, and the effects of the parameters on the PRL levels were analyzed. Results Compared with non-DM patients, the patients in the DM subgroup had lower PRL levels (P < 0.0001) and rather severe psychiatric symptoms (P = 0.016). Female, treated by risperidone, and high levels of triglyceride (TG) were faced with risk for HPRL (B = 26.31, t = 5.39, P < 0.0001; B = 19.52, t = 4.00, P < 0.0001; B = 2.71, t = 2.31, P = 0.022, respectively). Meanwhile, co-morbid DM and aripiprazole treatment were protective factors (B = 15.47, t = 3.05, P = 0.002; B = –23.77, t = –2.47, P = 0.014; respectively). Ultimately, in the DM subgroup, the dose of metformin was found to be a protective factor for HPRL (B = –0.01, t = –1.46, P = 0.047), while female and aripiprazole were risk factors (B = 16.06, t = 3.26, P = 0.001; B = 20.13, t = 2.57, P = 0.011; respectively). Conclusion Aripiprazole is a protective factor for HPRL in long-term hospitalized patients, whereas the female is a risk factor. Metformin is beneficial in reducing PRL levels in patients with co-morbid DM. More aggressive and effective interventions are required for preventing adverse drug reactions in women and patients with co-DM.